Synthesis and Biological Evaluation of Some New 2,4,6-Trisubstituted Pyrimidines - Sridhar, S.; Rajendra Prasad, Y.; Dinda, S.C. (Asian Journal of Chemistry, 2011)
In the present study, 3-acetyl-2,5-dimethylfuran on condensation with various aromatic and heterocyclic aldehydes in ethanolic KOH solution yielded the corresponding chalcones (3a-n). These chalcones were reacted with guanidine hydrochloride in presence of potassium hydroxide and ethanol to give pyrimidines (4a-n). All these compounds were characterized by IR, 1H NMR spectroscopic data and microanalyses. When these compounds were evaluated for antiinflammatory and antimicrobial activities, some of them were found to possess significant activity, when compared to standard drugs.